SARCOPENIA: FROM CLINICAL ASPECTS TO THERAPEUTIC POSSIBILITIES - Stefanovic, Katarina; Mihajlovic, Gordana; Despotovic, Nebojsa (Srpski medicinski časopis Lekarske komore, 2022)
In recent years, with the increase in life expectancy and the increasing number of elderly people, sarcopenia has been recognized as a separate entity and a new field in geriatric medicine. The European Working Group on Sarcopenia in Older People defined sarcopenia as a syndrome characterized by progressive and generalized loss of skeletal muscle mass, strength and consequently muscle function, which carries with it an increased risk of falls, disability, loss of work ability and premature death. Sarcopenia in the elderly is being given major research focus in many countries, due to its great impact on morbidity, mortality and health care costs. Despite its clinical importance, sarcopenia is still underrecognized in daily clinical practice, in part due to the lack of available diagnostic tests and unique diagnostic criteria, as well as the lack of clear treatment guidelines. Diagnosing sarcopenia requires assessment of muscle mass, muscle strength and physical performance. The treatment of sarcopenia includes various non-pharmacological and pharmacological approaches, and is primarily focused on resistance and strength exercises, with simultaneous nutritional support.